2016
DOI: 10.18016/ksujns.16383
|View full text |Cite
|
Sign up to set email alerts
|

Erzurum İli Hınıs İlçesi Sığırcılık İşletmelerinin Barınak Özellikleri Üzerine Bir Araştırma

Abstract: Bu araştırma, Erzurum ili Hınıs ilçesinde faaliyet gösteren sığırcılık işletmelerinin barınak özellikleri hakkında ayrıntılı bilgi edinmek üzere yürütülmüştür. Bu amaçla, 378 adet sığırcılık işletme sahibi ile yüz yüze anket yapılarak elde edilen veriler değerlendirilmiştir. Değişkenler arasındaki ilişkilerin belirlenmesi amacıyla da kikare testi yapılmıştır. Hınıs ilçesinde en sık görülen ahır tipinin bağlı duraksız kapalı ahır (% 51.5) olduğu, ahır yapısının işletme sahiplerinin sağlıklarını (% 88.8), inekle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 8 publications
1
7
0
Order By: Relevance
“…It was determined that the majority of the enterprises housed heifers, young cattle and dry cows together (90.4%), and only 9.6% of them housed them separately (Figure 3). The findings were found to agree with the findings of Aydın et al (2016) and Güler et al (2017). It was also determined that the choices of housing of heifers, calves, and dry cows together in the same barn were significantly (P<0.01) affected by the size of the farm and the education level of the farm owners in İspir district.…”
Section: Resultssupporting
confidence: 77%
See 4 more Smart Citations
“…It was determined that the majority of the enterprises housed heifers, young cattle and dry cows together (90.4%), and only 9.6% of them housed them separately (Figure 3). The findings were found to agree with the findings of Aydın et al (2016) and Güler et al (2017). It was also determined that the choices of housing of heifers, calves, and dry cows together in the same barn were significantly (P<0.01) affected by the size of the farm and the education level of the farm owners in İspir district.…”
Section: Resultssupporting
confidence: 77%
“…(Figure 4). Similarly, it was reported that among cattle enterprises 93.4% in Diyarbakır (Han and Bakır, 2010), 55.9% in Muş (Şeker et al, 2012), 79.7% in Niğde (Ünalan et al, 2013), 81.0% in Erzurum (Hınıs district) (Aydın et al, 2016), 77.3% Malatya provinces (Köseman and Şeker, 2016) and 65.0% in Uşak province (Demirhan and Yenilmez, 2019) did not use bedding material. As it can be seen from the literature reports and the results of the current study, the choice of bedding usage was considerably low in Turkey.…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations